Why the (dis)agreement? Family context and child–parent perspectives on health‐related quality of life and psychological problems in paediatric asthma. (5th May 2014) - Silva, N.; Crespo, C.; Carona, C.; Bullinger, M.; Canavarro, M. C.
Abstract Background Children's health‐related quality of life (HrQoL) and psychological problems are important outcomes to consider in clinical decision making in paediatric asthma. However, children's and parents' reports often differ. The present study aimed to examine the levels of agreement/disagreement between children's and parents' reports of HrQoL and psychological problems and to identify socio‐demographic, clinical and family variables associated with the extent and direction of (dis)agreement. Methods The sample comprised 279 dyads of Portuguese children with asthma who were between 8 and 18 years of age (M = 12.13; SD = 2.56) and one of their parents. The participants completed self‐ and proxy‐reported questionnaires on paediatric generic HrQoL (KIDSCREEN‐10), chronic‐generic HrQoL (DISABKIDS‐37) and psychological problems (Strengths and Difficulties Questionnaire). Children's and parents' perceptions of family relationships were measured with the Family Environment Scale and the caregiving burden was assessed using the Revised Burden Measure. Results The child–parent agreement on reported HrQoL and psychological problems was poor to moderate (intraclass correlation coefficients between 0.32 and 0.47). The rates of child–parent discrepancies ranged between 52.7% (psychological problems) and 68.8% (generic HrQoL), with 50.5% and 31.5% of the parents reporting worse generic and chronic‐generic HrQoL, respectively, and 33.3% reporting more psychological problems than their children. The extent and direction of disagreement were better explained by family factors than by socio‐demographic and clinical variables: a greater caregiving burden was associated with increased discrepancies in both directions and children's and parents' perceptions of less positive family relationships were associated with discrepancies in different directions. Conclusions Routine assessment of paediatric HrQoL and psychological problems in healthcare and research contexts should include self‐ and parent‐reported data as complementary sources of information, and also consider the family context. The additional cost of conducting a more in‐depth assessment of paediatric adaptation outcomes can be offset through more efficient allocation of health resources.